Genetic variation estimated in three shorea species by the RAPD analysis - Harada, Ko; Kinoshita, Akira; Ab Shukor, Nor Aini; Tachida, Hidenori; Yamazaki, Tsuneyuki (The Genetics Society of Japan, 1994)
Three species of Shorea (S. leprosula, S. acuminata and S. cursitii) were collected from a natural forest reserve of Malaysia and analyzed for genetic variation using the technique of random amplification of polymorphic DNA (RAPD) by the polymerase chain reaction (PCR). The average number of nucleotide substitutions was estimated. The nucleotide diversities within species were very similar and larger than those found in Drosophila melanogaster. The nucleotide divergences between these species are about 1.5 times the nucleotide diversities within the species, indicating that these species diverged from a common ancestor relatively recently.